2019
DOI: 10.3390/ijms21010092
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects and Mechanisms of Chitosan and Its Derivatives on Hypercholesterolemia in High-Fat Diet-Fed Rats

Abstract: The present study investigated and compared the effects of different molecular weights of chitosan (high molecular weight chitosan (HC) and low molecular weight chitosan (LC)) and its derivatives (chitosan oligosaccharide (CO)) on cholesterol regulation in high-fat (HF) diet-fed rats. A diet supplementation of 5% HC, 5% LC, or 5% CO for 8 weeks showed hypocholesterolemic potential in HF diet-fed rats. Unexpectedly, a 5% CO-supplemented diet exerted hepatic damage, producing increased levels of aspartate aminot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
5
24
0
1
Order By: Relevance
“…This results in not maintaining reasonably high intake of monounsaturated fats and fiber, olive oil and fish (ω-3 fatty acids), vegetable protein, fruit, coffee, or vitamin C [7,51]. A recent study showed that a supplementation with 5% chitosan oligosaccharide, a common food additive for weight loss, may cause liver damage via higher hepatic cholesterol accumulation and higher intestinal cholesterol uptake in high fat diet-fed rats [52]. A carbohydrate-restricted, high-fat diet increased LDLcholesterol concentrations because this effect of weight loss was related to the lack of suppression of both fasting and 24-h free fatty acids [53].…”
Section: Discussionmentioning
confidence: 99%
“…This results in not maintaining reasonably high intake of monounsaturated fats and fiber, olive oil and fish (ω-3 fatty acids), vegetable protein, fruit, coffee, or vitamin C [7,51]. A recent study showed that a supplementation with 5% chitosan oligosaccharide, a common food additive for weight loss, may cause liver damage via higher hepatic cholesterol accumulation and higher intestinal cholesterol uptake in high fat diet-fed rats [52]. A carbohydrate-restricted, high-fat diet increased LDLcholesterol concentrations because this effect of weight loss was related to the lack of suppression of both fasting and 24-h free fatty acids [53].…”
Section: Discussionmentioning
confidence: 99%
“…This results in not maintaining reasonably high intake of monounsaturated fats and ber, olive oil and sh (ω-3 fatty acids), vegetable protein, fruit, coffee, or vitamin C (7,48). A recent study showed that a supplementation with 5% chitosan oligosaccharide, a common food additive for weight loss, may cause liver damage via higher hepatic cholesterol accumulation and higher intestinal cholesterol uptake in high fat diet-fed rats (49). A carbohydrate-restricted, high-fat diet increased LDL-cholesterol concentrations because this effect of weight loss was related to the lack of suppression of both fasting and 24-h free fatty acids (50).…”
Section: Discussionmentioning
confidence: 99%
“…Evidently now is the time for experimental and clinical confirmation of statins applicability in COVID-19 treatment [111]. It is well known that chitosan also can decrease the content of cholesterol [113]. Chitosan prevents cholesterol deposition into erythrocyte membranes [114].…”
Section: Cholesterolmentioning
confidence: 99%